Aphanizomenon flos-aquae: A Biorefinery for Health and Energy—Unleashing Phycocyanin’s Power and Biogas Potential - Pilar Águila-Carricondo; Raquel García-García; Juan Pablo de la Roche; Pedro Luis Galán; Luis Fernando Bautista; Juan J. Espada; Gemma Vicente (Marine Drugs)
This study presents a biorefinery approach for Aphanizomenon flos-aquae, demonstrating its potential as a dual source for phycocyanin and biogas. The antioxidant capacity of the extract was evaluated using the ABTS•+ assay, while flow cytometry determined its cytotoxic effects on breast cancer (HCC1806) and brain glioma (U-118 MG) cell lines, comparing pure C-phycocyanin to the non-purified extract. The non-purified extract scavenged 77% of ABTS•+ radicals at 2.4 mg/mL, compared to 22% for pure C-phycocyanin. In U-118 MG cells, pure C-phycocyanin accounted for 55.5% of the 29.9 ± 6.1% total mortality observed with the non-purified extract at 0.75 mg/mL. HCC1806 cytotoxicity (80.9 ± 5.1% at 1 mg/mL) was attributed to synergistic effects of other extract components. The spent biomass was valorized through anaerobic digestion for biogas production, enhancing process sustainability. At a 2:1 inoculum-to-substrate ratio, the anaerobic digestion of the spent biomass yielded 447 ± 18 mL CH4/gVS, significantly higher than the 351 ± 19 mL CH4/gVS from the initial biomass. LCA estimated the environmental impacts of the A. flos-aquae biorefinery for phycocyanin production, targeting the cosmetic, food, and nutraceutical sectors, and highlighting the benefits of spent biomass valorization to produce biogas within a circular economy framework. This integrated approach demonstrates the potential of A. flos-aquae for the sustainable production of high-value compounds and renewable energy.